Engineered Reuse of DREDGED MARINE SOILS from Malaysian Waters 2 - Chee-Ming Chan; Mohammad Zawawi Rosman (Penerbit UTHM, 2022)
This is the second book in the series written to give an insight to some feasible techniques for reusing dredged marine soils. The reuse potential of the treated soils can be found in reclamation works as well as landfill liners. Admixed with stabilising agents and granular materials, the originally soft and weak dredged marine soils can be transformed into stable backfills in artificial land creation. The granular additions could be sourced from industrial or construction wastes, further enhancing the sustainable and responsible use of natural resources. For reuse in landfills, microbial activity in the soil serves as a bioindicator of contamination risks, especially from the leachate retention pond. In short, engineered solutions applied to the otherwise waste material could effectively give second lives to the dredged marine soils, minimising the need for customised dump sites, as well as additional transportation and operational costs in the long run.